2002
DOI: 10.1097/00024720-200202000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Sagittal Spinal and Pelvic Parameters in Asymptomatic Persons and Patients with Isthmic Spondylolisthesis

Abstract: Using a specialized orthopedic software package, the authors investigated the sagittal spinal shape and the position of the pelvis in the space in patients with isthmic spondylolisthesis and in persons with no such symptoms. Digitized lateral spinal radiographs of 30 healthy volunteers and 48 patients were evaluated. The absolute values and significant correlations between parameters were analyzed. The pelvic parameters correlated well with lordosis, which shows sagittal balance in the asymptomatic group. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
89
3
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(103 citation statements)
references
References 12 publications
3
89
3
8
Order By: Relevance
“…In a cohort of 39 subjects with spondylolysis and low-grade (I or II) spondylolisthesis, Marty et al [17] noted a greater PI and SS, and postulated (as have Labelle et al [11,12]) that this increased PI could predispose to spondylolisthesis, since PI is specific and remains constant for each individual after childhood. The same findings were reported by Rajnic et al [19] in a cohort of 48 adults with low-grade isthmic. In addition, Hanson et al [9] reported that PI was significantly higher in 40 patients with spondylolisthesis as compared with controls and PI was correlated with the grade of slipping.…”
Section: Discussionsupporting
confidence: 89%
“…In a cohort of 39 subjects with spondylolysis and low-grade (I or II) spondylolisthesis, Marty et al [17] noted a greater PI and SS, and postulated (as have Labelle et al [11,12]) that this increased PI could predispose to spondylolisthesis, since PI is specific and remains constant for each individual after childhood. The same findings were reported by Rajnic et al [19] in a cohort of 48 adults with low-grade isthmic. In addition, Hanson et al [9] reported that PI was significantly higher in 40 patients with spondylolisthesis as compared with controls and PI was correlated with the grade of slipping.…”
Section: Discussionsupporting
confidence: 89%
“…Another factor is the role an individual's sacropelvic geometry may play in these outcomes. Pelvic incidence has been shown to be associated with spondylolysis, progression of spondylolisthesis, and degree of degenerative disc disease at L5-S1 [14,23,30,34,42,43]. It could be possible that pelvic incidence or sacral inclination may have the same effect on spondylolysis at L4 and may account for some of the greater than predicted amount of degenerative disc disease we found in specimens with L4 lesions.…”
Section: Discussionmentioning
confidence: 76%
“…Toy et al [49] found sacral inclination and degenerative disc disease, and pelvic incidence and degenerative disc disease, to be associated at the L5-S1 level. Pelvic incidence has been shown to correlate with spondyloarthrosis [14], and spondylolysis and spondylolisthesis [23,30,34,42,43]. However, none of these previous articles mentioned the effect that pelvic incidence had on the L4-L5 motion segment.…”
Section: Discussionmentioning
confidence: 99%
“…It is accepted that PI becomes fixed with skeletal maturation and remains constant in adulthood, unless there is a pathological process that can modify the shape of the pelvis [6,9,10]. Deviations in pelvic morphology and subsequently higher values of PI were found to be associated with spondylolisthesis and idiopathic scoliosis [11][12][13][14][15][16]. Significantly lower PI was reported in patients with post-tuberculosis or congenital thoracic and thoracolumbar kyphosis [17].…”
Section: Introductionmentioning
confidence: 99%